The Increased Superoxide Dismuatase (SOD) In Mice Infected by Plasmodium Berghei ANKA Treated with Nanoparticle Extract of Beetroot (Beta Vulgaris L) - Fransisca Pramesshinta Hardimarta; Lisyani Budipradigda Suromo; Kis Djamiatun (RSUP Dr. Kariadi, 2024)
BACKGROUND: Malaria infection causes increased free radicals which leads to severity and decreases antioxidant activity, thus increasing the risk of severe malaria complications. Beetroot extract has active compounds that function as anti-inflammatory and antioxidants. Nanoparticles are a technology that can be used to improve drug delivery efficiency in smaller doses. AIMS: to prove the effectiveness of beetroot extract nanoparticles on SOD levels in mice infected with malaria and treated with artemisinin METHOD: An experimental study using a post-test-only randomized control group design. The research sample used 30 male Balb/c mice divided into 6 groups. Group 1 was the healthy group, group 2 was the infected group without treatment, group 3 was the infected group with artemisinin treatment, group 4 was the infected group with artemisinin treatment and 50 mg/kgBW/day beetroot extract nanoparticles, group 5 was the infected group with artemisinin treatment and 100 mg/kg BW/day beetroot extract nanoparticles, and group 6 was the infected group with artemisinin treatment and 200 mg/kg BW/day beetroot extract nanoparticles. Beetroot extract and artemisinin supplementation were given after parasitemia index > 1% and given for 4 days. On the 5th day after therapy, serum SOD levels were measured using ELISA. RESULT: The measurement of SOD levels in the artemisinin group supplemented with nanoparticle extracts of beetroot at doses 100-200 mg/KgBW were 21,48-21,59 ng/ml. Kruskal Wallis and Mann Whitney test showed that they are significantly higher serum SOD levels compared to the infected mice group (p<0.05). CONCLUSION: Supplementation of beetroot extract nanoparticles has an antioxidant effect by increasing SOD levels in mice infected with malaria and receiving artemisinin therapy.